(untitled) (Indian Journal of Animal Production and Management, 2024)
The knowledge of ingestive behaviour of cows and buffaloes is very important in improving cow wellbeing and performance. The ingestive behaviour of bovines has been classified into sucking behaviour, feeding, rumination and water drinking. Natural suckling performed for a total duration of one hour daily on an average for 5-8 times in a day is of great importance for the proper nourishment, health and welfare of calves. Deprivation of suckling has detrimental effect both of the mother and calves especially in native breeds of cows and buffaloes. Feeding both grazing and stall-feeding duration, frequency, the circadian patterns of grazing and feeding determine the feed intake and hence the production of the animals. Similarly, rumination which completes the process of feed ingestion, its duration, and frequency is important for proper feed utilization and hence animal performance. Length of manger space available and partioning of manger for individual cows helps reduce the competition at manger and thus improves animal productivity. Availability, temperature and quality of water for the drinking of cows and buffaloes are the important considerations for that improving water intake. This paper reviews the available literature on the ingestive behaviour especially of native cattle and buffaloes and discusses how this knowledge can be utilized for improving the production and welfare of these animals.